EXPLORING THE INTERSECTION BETWEEN ARTIFICIAL INTELLIGENCE AND THE PSYCHOLOGY OF CREATIVITY: A CASE STUDY OF THE MOST KNOWN ARTIFICIAL INTELLIGENCES - LAM-CAMPOS, Máximo Lui (2024)
This case study delves into the complex relationship between artificial intelligence (AI) and the psychology of creativity, using as a sample some of the most prominent artificial intelligences today. The creative capabilities of these AIs will be analyzed, exploring how they emulate or challenge human cognitive processes associated with the generation of innovative ideas. This case study seeks to shed light on the creative capacity of artificial intelligences, exploring their potential to contribute to fields such as literature, visual art, strategic games and music. Through detailed analysis of specific cases, it is hoped to provide a deeper understanding of the intersection between artificial intelligence and the psychology of creativity.